Pelaksanaan Kegiatan Membangun Desa di Desa Dulukapa, Kecamatan Sumalata Timur, Kabupaten Gorontalo Utara, melalui Kegiatan KKN Tematik - Aydalina, Regina Valentine; Mamu, Hartono (Universitas Negeri Gorontalo, 2024)
Thematic Community Service Program (KKN Tematik) in rural development is a Form of Learning Activity (FLA) that hones students' soft skills in partnership, interdisciplinary collaboration, and leadership in managing development programs in rural areas. The goal of Thematic Community Service Program (KKN Tematik) in rural development is to provide students with the opportunity to utilize their knowledge, technology, and skills by collaborating with various stakeholders in the field through student engagement and assisting in accelerating development in rural areas. This activity took place from September to November 2021 in Dulukapa Village, East Sumalata District, North Gorontalo Regency. The Thematic Community Service Program (KKN Tematik) conducted consisted of community assistance to accelerate COVID-19 vaccination, improvement of village infrastructure, and optimization of Early Childhood Education (PAUD) in the village. All activities were carried out successfully as expected.